ADVANCE performance
The coaching provided by ADVANCE performance utilises the latest heart rate training methods and builds programmes around the needs of each athlete we are involved with. Our success with a wide range of athletes has caused quite a stir! Within this site you will find details of the products and services available to you and guidance on how to get the best from your own heart rate training. You will also find copies of articles that Stuart Hale of ADVANCE performance has written for the UK's leading magazines, which include Today's Runner, Athletics Weekly, Triathlete Magazine and TRInews.